1999
DOI: 10.1007/s001340051004
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided thoracentesis in surgical intensive care patients

Abstract: Sir: To evaluate drainage volume, complications, and the diagnostic value of ultrasound-guided (US-guided) thoracentesis in a surgical intensive care unit (SICU), a prospective analysis was performed of all patients who had undergone thoracentesis in the SICU from January 1995 to December 1997. In addition, the impact of patient compliance on the complication rate was observed. Statistical analysis was carried out by the SPSS 8.0 software package using the Spearman rank test.Thoracentesis was performed under 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 3 publications
2
8
0
Order By: Relevance
“…A similar complication rate was found in a study of parapneumonic effusions in mechanically ventilated patients, with 2/94 (2%) of patients developing a haemothorax 48 . In a surgical ICU with a series of 135 patients having 338 procedures, the complication rate was again similar, with four patients (1.2%) developing pneumothoraces and four developing haemothoraces 54 …”
Section: Safety Of Ultrasound‐guided Thoracocentesissupporting
confidence: 78%
See 1 more Smart Citation
“…A similar complication rate was found in a study of parapneumonic effusions in mechanically ventilated patients, with 2/94 (2%) of patients developing a haemothorax 48 . In a surgical ICU with a series of 135 patients having 338 procedures, the complication rate was again similar, with four patients (1.2%) developing pneumothoraces and four developing haemothoraces 54 …”
Section: Safety Of Ultrasound‐guided Thoracocentesissupporting
confidence: 78%
“…48 In a surgical ICU with a series of 135 patients having 338 procedures, the complication rate was again similar, with four patients (1.2%) developing pneumothoraces and four developing haemothoraces. 54 In a systematic review of studies of thoracocentesis in ventilated patients, Goligher et al 11 found the pooled risk of pneumothorax was 3.4% (95% confidence interval: 1.7-6.5)-20 events in 14 studies including 965 patients. The pooled risk of haemothorax was 1.6% (95% confidence interval: 0.8-3.3%)four events in 10 studies with 721 patients.…”
Section: Safety Of Ultrasound-guided Thoracocentesismentioning
confidence: 99%
“…Among 187 sonographically guided procedures, the success rate approached 95%, with a complication rate of only 3% (23). A liberal use of ultrasonography to guide thoracentesis has recently been advocated to increase the safety of this invasive procedure, especially in ventilated ICU patients (10,11,21).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative assessment of the volume of pleural effusions would be crucial to help select critically ill patients for thoracentesis. Pleural ultrasonography has been shown to efficiently guide thoracentesis in ICU patients (10,11) and to predict the volume of pleural effusion in ambulatory patients (12). However, its ability to quantitatively assess pleural effusions in the ICU setting has not yet been evaluated.…”
mentioning
confidence: 99%
“…Barnes et al [24] and Gervais et al [26], in retrospective studies on ultrasound-guided thoracentesis performed by interventional radiologists, reported pneumothorax rates of 4.9% and 2.3%, respectively. Petersen et al [27] reported a series of 338 ultrasoundguided thoracentesis in the ICU, with four pneumothoraces (1.2%). Lichtenstein et al [28] and Mayo et al [29] reported pneumothorax rates in patients receiving mechanical ventilation of 0 and 1.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%